Implementation of Guided Inquiry Learning Model Based on Local Wisdom of Tapai Jringkeng to Improve Students' Critical Thinking Skills - Rosyidah, Naila; Setiawan, Beni; Romadhoni, Mohammad (Journal of Innovation in Educational and Cultural Research, 2026)
Higher-order thinking skills are essential for students in the twenty-first century, with critical thinking being one of the most important. Despite its significance, Indonesian students' critical thinking skills often fall short of international standards. This may be attributed to science education that frequently overlooks socio-cultural environments. By integrating guided inquiry learning models with local wisdom, specifically tapai jringkeng, this study aims to examine the improvement of critical thinking skills in the 9-B class at SMPN 1 Kotaanyar. The research utilized a one-group pretest-posttest design involving 23 students. Data were gathered using an essay-based test consisting of five questions and analyzed with the N-gain formula. The findings revealed an N-gain score of 0.77, categorized as a high level, indicating a significant improvement in students' critical thinking skills. The study suggests that incorporating local wisdom into inquiry-based learning can enhance cognitive engagement and foster a deeper understanding of the context. Additionally, this research contributes to science education by offering a culturally responsive teaching model that fosters critical thinking through the inclusion of local wisdom.